Business readiness towards implementation of goods and services tax in Malaysia / Khairun Nisa Ibrahim and Nur Syafiqah Mustaffa - Ibrahim, Khairun Nisa; Mustaffa, Nur Syafiqah (2014)
This research focused on factors that influence the business readiness towards implementation of goods and services tax (GST) in Malaysia. In order to guide this research, there are four factors that contribute to the business readiness towards implementation of GST which are GST team, training program, goods and services pricing and IT system. The objectives of this study were (1) to investigate the business readiness for implementation of GST in term of their GST teams, training program, goods and services pricing and IT system, (2) to measure the association between business initiatives in set-up the GST team, training program, goods and services pricing and improving IT system towards the business readiness on GST implementation and (3) to investigate the factors that influence business readiness towards implementation of goods and services tax (GST). The respondents were participants who attended the Royal Malaysian Customs seminar on the implementation of GST in business in Malaysia. A total of 125 questionnaires were distributed to the respondents. The process of analyzing and interpreting data has been presented by figures and tables using method of reliability analysis, frequency analysis, Pearson correlative and regression analysis. In overall, the business in Malaysia needs to improve their readiness on GST before it implementation on April 2015